Evaluating Domestic Violence Initiatives - Parmar, Alpa (The British journal of criminology, 2007)
This paper critiques the approach of identifying best practice' projects and discusses the problem with simply transferring projects into different contexts. The argument is illustrated by explaining the evaluation process of three domestic violence projects which all had the same aim, which was to reduce domestic violence. The evaluated projects all delivered advocacy programmes and were located in disadvantaged areas in the United Kingdom. A more suitable evaluation approach is proposed whereby practice principles are transferred rather than projects and this is presented in the form of a practice model'